Root Development of Crops under Irrigation in the Arid Zone - Singh, Atar (Annals of Arid Zone, 2016)
Root observations recorded in field crops during kharif 1973 and rabi 1973-74 season indicated that the calcareous substratum in soils of Pali ( Rajasthan) docs not act as a barrier to root growth and ramification. All the crops studied made full root development and exhibited yield potential. Most of the roots of urd, sorghum, wheat, barley and cumin crops were found in the upper 15 em soil. Crops like chilly, maize, safflower and sunflower expanded their root zone upto 30 cm soil depth and made full growth. Roots of cotton, arhar and raya permeated upto 46 cm soil, made optimum growth and expressed yeild potential.